A BRIEF CLASSIFICATION OF ENGLISH TOPONYMS - Mirzayeva Dilshoda Ikromjonovna; Sidikova Saidakhon Akmaljon kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: Toponyms (place names) represent language units denoting elements of topographic environment. The relevance of the study is caused by the need to develop the theory of toponymy and to systematize all the existing toponymic classifications. Place names have a complicated (multidimensional) nature, which should be taken into account while classifying them. This article is an attempt to highlight various principles according to which it is possible to group the place names.